Supervised Physiotherapy Vs. Conventional And Mhealth-Driven Home Exercise: A Tri-Modal Comparison Of Body Composition And Lipid Profile Changes In Borderline Obesity - Balakrishna , Bathala; Alagesan, Jagatheesan (Journal of Neonatal Surgery, 2025)
Background: Borderline obesity represents a critical window where timely lifestyle-based interventions can reverse metabolic progression. Exercise prescription delivered via mHealth technologies is increasingly used, yet comparative evidence against supervised physiotherapy remains limited. Objective: To compare the effects of supervised physiotherapy, conventional home exercise, and mHealth-driven home exercise on body composition and lipid profiles in borderline-obese adults. Methods: A 12-week randomized controlled tri-modal trial enrolled 90 participants (BMI 25–29.9 kg/m²) allocated to: (1) supervised physiotherapy (SP), (2) conventional home exercise (CHE), or (3) mHealth-assisted home exercise (mHE). Body composition (BMI, body fat %, visceral fat), waist-hip ratio, and lipid markers (TC, TG, LDL-C, HDL-C) were measured at baseline and 12 weeks. Statistical analysis included ANOVA. Results: SP demonstrated the greatest reduction in body fat%, visceral fat and LDL-C compared with CHE and mHE (p<0.05). mHE showed significantly better adherence and outcomes than CHE, particularly for HDL-C improvement. CHE achieved modest but significant changes. Conclusion: Supervised physiotherapy was most effective, whereas mHealth-driven exercise outperformed conventional home exercise. mHealth tools may bridge the gap where supervised models are inaccessible